El impediemte dirimente del impotente en el matrimonio,afecta los derechos y libertades de las personas - Risco Zambrano, Santa Rosalia (2013)
This legal research, entitled "The powerless absolute impediment of marriage, affect the rights and freedoms of individuals" was the result of a thorough analysis of the regulatory provisions of the Civil Code concerning the rights of powerless people, a situation that nullity because the marriage contracted by these people, a constitutional right is violated by Article 95, no. 4 of the Civil Code, where it is discriminated against by their health status, and thus their right to form a family through adoption, as well as the right to test or bequeath your estate to your heirs. The research objectives guided the entire research process literature, and the hypothesis, the field research process. Results that were obtained by conducting surveys and interviews, data and information that allowed confront the hypothesis, namely: "The reform of the Arts. 95 and 102 of the Civil Code regarding the impediments dissolving marriage and the feasts of the same, will prevent the infringement of the rights and freedoms of individuals powerless to be considered equal before the law ", was positive, it was shown that such precepts law should be reformed to avoid infringement of the constitutional rights of powerless people. The proposed legal reform to Article 95 and 102 of the Civil Code, in sections above, aims to forewarn that the constitutional right to non-discrimination of persons is violated by lower-level rules that contravene express constitutional provisions, as all before the law enjoy equal rights and opportunities. The health condition of the powerless can not be sanctioned, as indeed it is, to be considered A marriage contracted with